The α(2a) Adrenergic Receptor Subtype Mediates Spinal Analgesia Evoked by α(2) Agonists and Is Necessary for Spinal Adrenergic–Opioid Synergy - Stone, Laura S. (J Neurosci, 1997)
Agonists acting at α(2) adrenergic and opioid receptors have analgesic properties and act synergistically when co-administered in the spinal cord; this synergy may also contribute to the potency and efficacy of spinally administered morphine. The lack of subtype-selective pharmacological agents has previously impeded the definition of the adrenergic receptor subtype(s) mediating these effects. We therefore exploited a genetically modified mouse line expressing a point mutation (D79N) in the α(2a) adrenergic receptor (α(2a)AR) to investigate the role of the α(2a)AR in α(2) agonist-evoked analgesia and adrenergic–opioid synergy. In the tail-flick test, intrathecal administration of UK 14,304, a nonsubtype-selective α(2)AR agonist, had no analgesic effect in D79N mice, whereas the analgesic potency of morphine (intrathecal) in this assay was not affected by the mutation. The mutation also decreased α(2)-agonist-mediated spinal analgesia and blocked the synergy seen in wild-type mice with both the δ-opioid agonist deltorphin II and the μ-opioid agonist [d-ALA(2),N-Me-Phe(4),Gly-ol(5)]-Enkephalin (DAMGO) in the substance P behavioral test. In addition, the potency of spinally administered morphine was decreased in this test, suggesting that activation of descending noradrenergic systems impinging on the α(2a)AR contributes to morphine-induced spinal inhibition in this model. These results demonstrate that the α(2a)AR subtype is the primary mediator of α(2) adrenergic spinal analgesia and is necessary for analgesic synergy with opioids. Thus, combination therapies targeting the α(2a)AR and opioid receptors may prove useful in maximizing the analgesic efficacy of opioids while decreasing total dose requirements.